Concurrent use of statins decreases major bleeding and intracerebral hemorrhage in non-valvular atrial fibrillation patients taking direct oral anticoagulants—A nationwide cohort study - Wu, Hsin-Hsu; Chang, Shang-Hung; Lee, Tsong-Hai; Tu, Hui-Tzu; Liu, Chi-Hung; Chang, Ting-Yu (Frontiers in Cardiovascular Medicine, 2022)
Background Statins are frequently prescribed with direct oral anticoagulants (DOACs), and previous studies have raised concerns about the increased risk of intracerebral hemorrhage or other major bleeding in concurrent statins and DOACs use. The objective of this study is to evaluate the risk of major bleeding in non-valvular atrial fibrillation patients taking DOACs with or without statins. Methods This nationwide, retrospective cohort study used data from the Taiwan National Health Insurance Research Database, enrolled a total of 90,731 non-valvular atrial fibrillation patients receiving rivaroxaban, dabigatran, apixaban or edoxaban from January 1st, 2012 to December 31st, 2017. Major bleeding was defined as a hospitalization or emergency department visit with a primary diagnosis of intracerebral hemorrhage, gastrointestinal tract bleeding, urogenital tract bleeding, or other sites of bleeding. Adjusted incidence rate ratios (IRR) and differences of major bleeding between person-quarters of DOACs with or without statins were estimated using a Poisson regression and inverse probability of treatment weighting using the propensity score. Results 50,854 (56.0%) of them were male with a mean age of 74.9 (SD, 10.4) years. Using DOACs without statins as a reference, the adjusted IRR for all major bleedings in concurrent use of DOACs and statins was 0.8 (95% CI 0.72–0.81). Lower major bleeding risk was seen in both low-to-moderate-intensity statins (IRR: 0.8, 95% CI 0.74–0.84) and high-intensity statins (IRR: 0.8, 95% CI 0.74–0.88). Concurrent use of DOACs and statins decreased the risk for intracerebral hemorrhage with an IRR of 0.8 (95% CI 0.66–0.93), and gastrointestinal tract bleeding with an IRR of 0.7 (95% CI 0.69–0.79). The protective effect of statins on intracerebral hemorrhage was observed only in female patients (IRR 0.67, 95% CI 0.51–0.89), but not in male patients (IRR 0.87, 95% CI 0.70–1.08). Conclusions Among non-valvular atrial fibrillation patients who were taking DOACs, concurrent use of statins decreased major bleeding risk, including intracerebral hemorrhage and gastrointestinal tract bleeding. Considering this and other cardioprotective effects, statins should be considered in all eligible patients prescribed with DOACs.